The Development of Packaging for Klumkapiklongdanchumchon 3 Community Enterprise Klong Dan Subdistrict Bang Bo District Samut Prakan Province - Yannawit Thiennararoj; Chanhathai Kerdsriserm; Apichat Sukcharoenkana (King Mongkut's Agricultural Journal, 2026)
This research aimed to 1) study the problems and needs regarding packaging design for the Klong Dan Shrimp Paste Community Enterprise Group 3, located in Klong Dan Subdistrict, Bang Bo District, Samut Prakan Province, 2) develop packaging for the community enterprise group, and 3) assess members’ satisfaction with the developed packaging design. The study employed a mixed methods research approach, integrating both qualitative and quantitative methods, with a total of 9 participants. A participatory action research process was applied throughout the study. Data collection instruments included in-depth interviews, a satisfaction questionnaire, and focus group discussions. Quantitative data were analyzed using descriptive statistics including frequency, percentage, mean, and standard deviation. The findings revealed that the community enterprise group lacked suitable packaging for use as a local souvenir product. The group expressed the need for packaging made from paper, in a rectangular box shape with a handle, foldable for convenient transport, stackable, and durable. The packaging was designed in a light brown color with a white label. The label contained product details including: the recipe for shrimp paste chili dip, list of ingredients, production and expiration dates, a brief history of the community enterprise, QR code, production location, and a background image of the group’s geographical location according to the satisfaction assessment, the first packaging design received the highest overall satisfaction (μ = 4.57, S.D. = 0.22). In terms of specific elements, the color received the highest level of satisfaction, followed by the label design, while the lowest satisfaction was found in terms of functional attributes.This packaging development significantly enhanced the product’s market value, increasing its price from 60 THB to 159 THB. The newly designed packaging emphasized modernity, convenience, and trustworthiness, contributing to greater consumer appeal. Moreover, the exchange of ideas among group members during the research process laid a strong foundation for the sustainable development of the community enterprise.
Keywords: Consumer Packaging Perceptions and Trends; Waste Management and Recycling; Agricultural and Environmental Management